Digital Technologies Are a Strong Basis for Improving the Statistical Activities of the Republic of Uzbekistan - B. A. Begalov; I. E. Zhukovskaya; Sh. G. Odilov (Открытое образование (Москва), 2023)
Purpose of the study. The main purpose of this article is to identify the main directions, means and methods of applying digital technological solutions in the static activities of the Republic of Uzbekistan and develop new recommendations for further improvement of this area of the national economy in the context of digital transformation of the world economic system.Materials and methods. When writing this article, the authors used the methods of system analysis, synthesis, induction, deduction, methods of working with computer networks, digital services and platforms, special methods and tools necessary for working with a statistical information system, statistical, optimization and software methods for working with the portal of the Agency of Statistics under the President of the Republic of Uzbekistan.Results. The authors of the article studied modern scientific and practical approaches to the effective use of digital technological solutions in the field of statistics, both on a global scale and in the Republic of Uzbekistan. Based on the conducted research, the authors concluded that in order to improve the national statistical system of the Republic of Uzbekistan, it is necessary to widely use advanced technological solutions using a full range of digital mechanisms, including innovative approaches to automating the processes of collecting and processing statistical information, creating the possibility of searching and obtaining statistical and analytical data in an interactive form for short periods of time, organizing interaction between statistical bodies and other ministries and departments of the country.The authors of the paper also noted that all processes for the effective introduction of digital technologies in the statistical sphere are carried out within the framework of the «Digital Uzbekistan – 2030» strategy and in accordance with the decree of the President of the Republic of Uzbekistan. In particular, the Agency of Statistics under the President of the Republic of Uzbekistan was entrusted with certain tasks, such as improving information systems for storing, processing and presenting statistical data, platforms for the unified state register of enterprises and organizations, as well as automating population registration processes. As part of the implementation of these tasks, a lot of work is being done to in-depth study of new areas and modern technologies in the field of the digital economy and e-government for their implementation in statistical activities.Conclusion. Modern world trends in the effective implementation of digital technologies in the processes of collecting, processing, transmitting and storing information in various sectors and areas of the world economy are also firmly included in the sphere of statistical activity of the Republic of Uzbekistan. As practice shows, at present, digital web services, software systems, information systems based on the use of digital devices and technologies are already operating in the field of statistics of Uzbekistan. But, along with the already existing achievements in the application of digital solutions in the field of statistics of the Republic of Uzbekistan, the methodology for the effective use of digital mechanisms and the organization of interdepartmental information interaction is being improved in order to enhance the quality of information exchange of data to develop optimal management decisions and increase the competitiveness of the national economy of the Republic of Uzbekistan.